Encoding Pleasant and Unpleasant Expression of the Architectural Window Shapes: An ERP Study - Naghibi Rad, Parastou; Shahroudi, Abbas Ali; Shabani, Hamed; Ajami, Sahar; Lashgari, Reza (Frontiers in Behavioral Neuroscience, 2019)
The evaluation of building facades is one of the most important elements in built environments for helping architects and professionals develop future designs. The form or shape of windows in building facades has direct impacts on perceivers’ affective state and emotions. To understand the impacts of geometric windows on the subject’s feedback and cortical activity, psychophysics experiments and EEG recordings were measured from the participants. Our behavioral results show a distinguished categorization of the window shapes as the pleasant and unpleasant stimuli. The rectangular, square, circular and semi-circular arch were determined as the pleasant window shapes, while the triangular and triangular arch window shapes were distinguished as the unpleasant. Furthermore, event related potential (ERP) components (N1, P2 and P3) were investigated to determine the influence of window shapes on the local brain activity. To measure reliable cortical responses, a Butterworth notch filter (50 Hz), the band pass (0.1-60 Hz), and finite impulse response were employed to remove the artifacts. The present electrophysiological results show increased activity for unpleasant in comparison to the pleasant windows (p<0.05, Rank Sum test) in both frontal (for P2 component) and posterio-occipital (ERP amplitudes; the N1 through to the P3 peak) channels. The ERP amplitudes of the right hemisphere were significantly larger than in the left hemisphere, not only in responding to the unpleasant (p<0.001) but also to the pleasant window stimuli (p<0.001, Sing Rank test). However, the unpleasant stimuli significantly evoked larger ERP amplitude than the pleasant stimuli. Moreover, the significance ERPP2 amplitude was more distinguished for unpleasant (p=0.01, Sing Rank test) than pleasant windows (p=0.01, Rank Sum test) between frontal and central cortical lobes. Overall, our behavioral and electrophysiological studies demonstrate a distinguished categorization of pleasant and unpleasant window shapes and more significant ERP modulations in the right than left hemisphere for unpleasant windows compared to pleasant ones.